THE FUNCTIONS OF ADVERTISEMENT SLOGAN IN THE BILLBOARD - AMBARWATI, SEPTIN; ANNANINGTYAS, CUCUT (Politeknik Harapan Bangsa Surakarta, 2020)
There are three problems statements in this research (1) what is the use of language in advertising (2) what are the functions of slogan on advertising and (3) what is the purpose of the advertiser use unique slogan on advertising. This research is a qualitative research. The function of this research is to describe language that is used in the slogan by using words and explanation. The data used on this research, which will use pragmatics analysis and implicate are taken from slogans advertisement in billboard. The data is taken from October – December 2015. Before analyzing, the researcher takes the picture data and out of collecting. After collecting data, next step is data analysis with pragmatics and to consider context on this analysis, another that the writer also searches the language functions on the slogan. Based on the analysis, the writer summarizes that the use language advertisement is unique language that advertisement be unique and interesting, usually the producer uses the brief language, no completed language but has the meaning, sometime they use foreign language. There are some slogan function that are (a) information, (b) persuasive, (c) educate, (d) entertain and more important the use by producer is the persuasive function because almost all the advertisement which made by advertiser always persuade to society to be consumer a product, although the slogan advertisement do not uses the word which persuade. The purpose of the advertisers use language in advertisement as which are found on billboard is to get people’s attention so that they will buy this product soon.